2022
DOI: 10.3389/fonc.2022.836803
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Oral Cancer: A Novel Approach

Abstract: BackgroundOral squamous cell carcinoma (OSCC) is a common head and neck cancer with high morbidity and mortality. Currently, treatment decisions are guided by TNM staging, which omits important negative prognosticators such as lymphovascular invasion, perineural invasion (PNI), and histologic differentiation. We proposed nomogram models based on adverse pathological features to identify candidates suitable for treatment escalation within each risk group according to the National Comprehensive Cancer Network (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The pathological type of all the patients in our study was squamous cell carcinoma. Recently, some researchers found that the PNI index and serum AGR level are significantly related to the OS of patients with esophageal cancer [ 34 , 35 ], oral cancer [ 36 , 37 ], and laryngeal cancer [ 38 , 39 ]. The researchers conducted a multivariate analysis of the PNI index and serum AGR level with the patients’ comorbidities, age, and other factors and found that both the PNI and the AGR were independent predictors of postoperative OS, which is consistent with our research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological type of all the patients in our study was squamous cell carcinoma. Recently, some researchers found that the PNI index and serum AGR level are significantly related to the OS of patients with esophageal cancer [ 34 , 35 ], oral cancer [ 36 , 37 ], and laryngeal cancer [ 38 , 39 ]. The researchers conducted a multivariate analysis of the PNI index and serum AGR level with the patients’ comorbidities, age, and other factors and found that both the PNI and the AGR were independent predictors of postoperative OS, which is consistent with our research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…We further found that high-risk features may be additive, with 2 high risk features imparting worse prognosis than 1 high-risk feature. Previous studies in patients with OP and OC similarly showed that composite risk scores that incorporate multiple pathological features can improve prognostic risk stratification.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is no universal definition of high-risk characteristics for OSCC, and in many situations, the clinical staging is not able of differentiating tumors with more aggressive behavior, that would benefit from specific therapeutic approaches. [5][6][7] Some histopathological features, besides depth of invasion and extranodal extension, have been associated with poor prognosis and in those cases, adjuvant treatment is frequently recommended. 8,9 Among those features are the infiltration of the neural structures.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a meticulous evaluation of the clinical, radiographic and pathological features, such as the depth of invasion and extranodal extension, 4 is performed to properly stage the patients with OSCC in order to select the optimal therapeutic protocol. However, there is no universal definition of high‐risk characteristics for OSCC, and in many situations, the clinical staging is not able of differentiating tumors with more aggressive behavior, that would benefit from specific therapeutic approaches 5–7 . Some histopathological features, besides depth of invasion and extranodal extension, have been associated with poor prognosis and in those cases, adjuvant treatment is frequently recommended 8,9 .…”
Section: Introductionmentioning
confidence: 99%